An Emergency Port Decision-Making Method for Maritime Accidents in Arctic Waters - Ting Wang; Xiaoxue Ma; Laihao Ma; Yulan Zhao (Journal of Marine Science and Engineering, 2023)
The complex and variable hydro-meteorological conditions in Arctic waters and scattered and limited port infrastructures pose a great threat and challenge to Arctic emergency search and rescue. It is crucial to determine an available and effective emergency port for rescue in the event of a maritime accident occurring in Arctic waters. In the present study, a directed-weighted emergency port network consisting of maritime accident nodes and port nodes for maritime accident-prone areas in Arctic waters is developed based on complex network theory. For this, the maritime accident nodes are identified by using a K-means clustering algorithm based on historical accident data; the port nodes are determined by screening of the port location and scale; the weights for edges between accident nodes and port nodes are characterized in terms of ERT (emergency rescue time) and PEC (port emergency capacity), and the PECs for different emergency ports along Arctic waters are acquired by entropy-weighted TOPSIS. With the developed emergency port network, the topological properties associated with the accident nodes, port nodes, and the edge weights between accident nodes and port nodes are analyzed. What is more, the emergency ports for each maritime accident point occurring in Arctic waters are obtained and ranked.